Growing old with esteem : Chengdu LONG LIVE's journey from community care to elderly-oriented service - Wang, Jianying; Xu, Jingyue (London : Renmin University, 2018)
LONG LIVE, founded in 2011, is one of the earliest social enterprises that have entered the community and home care industry. Its business scope has developed from the community care center and social service to the appropriated aging transformation, and it further extended to the appropriated aging assessment and big-data applications. Under the support of the appropriated aging platform management system, LONG LIVE started in Chengdu and is now spreading across the country by adopting the franchise mode in 2017. After obtaining the first round of angel investment, LONG LIVE also faced the strategic choice between focusing on its main business and implementing diversification. This case analyzes the process of LONG LIVE developing to a diversified industry at the perspective of company-level strategy, using Ansoff Matrix as the main analysis tool, at the same time, combining with the core competence theory. This case aims at allowing the students to analyze the business development mode of LONG LIVE, while at the same time guiding them to think about the future development of the company as a decision maker.
Originally Published InWang, J., & Xu, J. (2018). Growing Old with Esteem-Chengdu LONG LIVE's Journey from Community Care to Elderly-Oriented Service. Beijing, China: Renmin University Business School.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Diversification in industry; Community health services; Older people -- Medical care